2022
DOI: 10.7324/japs.2022.121004
|View full text |Cite
|
Sign up to set email alerts
|

A triterpenoid friedelan-3\�-ol isolated from Euphorbia lactea exhibited cytotoxic activity against HN22 cells by inducing an S-phase cell cycle arrest

Abstract: The anticancer activity of Euphorbia lactea Haw. (E. lactea) has been observed by our lab and other research groups; however, the identity of the bioactive compounds harboring the anticancer effect remains unknown. Here, we report the first isolation of four triterpenoidal compounds, i.e., friedelin [1], friedelan-3β-ol [2], taraxerol [3], and friedelan-3α-ol [4], from the n-hexane fraction of the E. lactea extract. The cytotoxic activities of these compounds were investigated in several cancer cell lines, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…Cynsaccatol (50) isolated from E. lathyris shows the greatest effect on the inhibition of the production of NO for macrophages stimulated with LPS. (4R,5S,8S,9R,10S,13R,16S)ent-16α,17-dihydroxy-19-tigloyloxykauran-3-one (248) and Euphorbia factors L1 and L3 have good cytotoxic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Cynsaccatol (50) isolated from E. lathyris shows the greatest effect on the inhibition of the production of NO for macrophages stimulated with LPS. (4R,5S,8S,9R,10S,13R,16S)ent-16α,17-dihydroxy-19-tigloyloxykauran-3-one (248) and Euphorbia factors L1 and L3 have good cytotoxic activity.…”
Section: Discussionmentioning
confidence: 99%
“…No previous data were found on the effects of E. resinifera and E. echinus extracts in human colon cancer cells, and the studies about the colon cancer effects of herbal extracts on colorectal cancers were limited. Previous reports by other researchers have documented the anti-migration of other Euphorbia species, including the hydroalcoholic extract of E. lacteal , which showed maximum inhibition (about 40%) at the concentration of 125 µg/ml against the migration of HN22 cells [ 64 ]. Another study on an ethanolic extract from seeds of E. lathyris showed a reduction in the migration capacity of 18.68% after 72 h of colon cancer cells (T84 cell line) [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in in vivo studies, it significantly inhibited TNBC tumor growth without causing side effects. Wongprayoon et al [ 149 ] noted that Euphorbia lactea triterpenoid friedelan-3β-ol was cytotoxic to several cancer cell lines, including HN22, HepG2, HCT116, and HeLa. Furthermore, the authors showed that the compound induced S-phase cell cycle arrest in HN22 cells without inducing apoptosis at the same concentration and exposure time.…”
Section: The Euphorbiaceae Family Of Plantsmentioning
confidence: 99%